Folded Stones: Tied Up Tree - Baert, Barbara; Mits, Trees De (Leuven Acco, 2009)
The project Navel-Body-Skin is a comparative and interdisciplinary research into the meaning of ceramics as an archetype in visual anthropology. The project tackles various issues, including the relationship between ceramics and the artist's body, the archetype of ceramics rooted in the idea of imprint and rotation, and the relationship between ceramics and other media. These questions result in artistic and theoretic experiments in Japan and Iceland. The texts and images in this cahier involve a momentum during the researchers' project and their development towardsa better understanding of what happens when the visual medium emerges out of formless matter such as clay. Barbara Baert call this secret 'iconogenesis'. Trees de Mits calls it the process of probing and interpreting reality of the 'body', the 'navel', the 'skin'.
Keywords: 21st Century (2001-2100); Fine art; Ceramic; Artistic research; Interdisciplinarity